Visual Inspection of Acetic Acid (VIA) as a Promising Standard for Cervical Cancer Screening: Inspeksi Visual dengan Asam Asetat (IVA) sebagai Standar Metode Skrining Kanker Serviks yang Menjanjikan - Tofan W Utami; Laila Nuranna; Marendra Mahathir; Alexander AW Peters; Gert J Fleuren; Michelle Osse; Sigit Purbadi (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To evaluate the